(untitled) (Bangladesh Journal of Zoology, 2016)
An experiment was conducted to develop a culture system for producing brackishwater shrimp, Penaeus monodon, at a management strategy affordable for marginal to medium farmers. Shrimp was produced by two cropping patterns viz., short cycle (60 days) double crops and long cycle (120 days) single crop each at three stocking densities viz., 3, 5, 7 nos./m2. The analysis of results revealed that production of shrimp of 913.57 - 1429.38 kg/ha in long cycle single crop was higher than that of 804.42 - 1296.87 kg/ha in aggregate of short cycle double crops at 3 - 5 nos./m2 density, but at 7 nos./m2 density, production of shrimp of 1899.39 kg/ha was higher in short cycle double crops than that of 1857.31 kg/ha in long cycle single crop. The differences in production between two cropping patterns at different densities were not significant. Gross margin was higher in high stocking ponds in both short and long cycle cropping pattern and it was 1.75 - 2.24 times higher in long cycle culture than that short cycle culture. However, considering higher benefit cost ratio and requirement of supply of oxygen for the production management, it can be surmised that production of shrimp in short cycle double crops at 5 nos./m2 densities will be better affordable for marginal to medium farmers having limited resource. Bangladesh J. Zool. 44(1): 31-40, 2016